Forage Plant Species and Pasture Capacity in Post Coal Mine Land, Margahayu Village, Kutai Kartanegara Regency - Muhammad Ubaidillah; Daru, Taufan Purwokusumaning; Fajrih, Nurul; Safitri, Apdila (Journal of Agriprecision & Social Impact, 2024)
Margahayu Village is one of the villages located in Loa Kulu Sub-district, Kutai Kartanegara Regency, which is a coal mining area. The post-coal mine reclamation land is mostly utilized by the local community as a Bali cattle pasture. In order for the pasture to be sustainable, it is necessary to know information about the type of forage plant and the carrying capacity of the pasture. This study aims to determine the types of forage plants that grow naturally and the carrying capacity of the pasture in Margahayu Village, Kutai Kartanegara Regency. The method used in this research is the exploratory method, by taking a snapshot using a quadrant size of 1 m x 1 m as many as 20 quadrants. The results showed that the pasture in post-mining land, Margahayu Village obtained 26 different species from 13 families. The dominant forage plant species in the pasture of Margahayu Village is Paspalum conjugatum with an IVI of 98.4% and a carrying capacity of 2.57 AU ha-1 year-1. The pastures in Margahayu Village can still accommodate 667.06 AU or equivalent to 667 cows.